(untitled) (CIPEEX, 2025)
This paper aims to analyze judicial conciliation and mediation through criteria of effectiveness, speed and reduction of demands specifically within the scope of the Court of Justice of Goiás. Initially, it seeks to conceptualize and highlight the relevance of the constitutional principles that govern Brazilian civil procedural law, such as speed and effectiveness, due process and, mainly for the purposes of this research, respect for the self-regulation of will. The latter, which concerns the freedom of the parties within the process, guarantees the formalization of procedural transactions, of which self-composition stands out. As well identified, the TJGO has received several awards from the National Council of Justice for the creation of incentives and its productivity regarding the National Conciliation Week. The research identified that the conduct of the aforementioned Court contributed to the results achieved, which, despite being negatively distant from the growth in demands, are considered economically satisfactory.